Study on Sensitivity Evaluation and Mechanism of Offshore Fluvial Reservoir - Tan, Jie; Tan, Jie; Yang, Dongdong; Guo, Jingmin; Peng, Qin; Sun, Enhui (Journal of Theory and Practice in Engineering and Technology, 2024)
The CFD oilfield is located in the western waters of the Bohai Sea, and the reservoir rock types are mainly lithic feldspar sandstone, followed by feldspar lithic sandstone, belonging to high porosity to medium high permeability reservoirs. During the process of water injection development, the production capacity of oil wells continues to decline. The effect of injecting water to increase oil is poor. This study conducted rock mineralogical analysis such as casting thin sections and scanning electron microscopy based on on-site data. Through core experiments, the sensitivity of the reservoir was evaluated, and data analysis showed that clay minerals damage the reservoir in the form of swelling, particle transport, etc. Theoretically, the damage mode of clay minerals to the oil reservoir was analyzed. Provide a basis for the development of similar oil fields.